Provision and delivery of survivorship care for adult patients with haematological malignancies: A scoping review protocol. - Zoe-Anne V Baldwin; Steph Busby; David Allsup; Judith Cohen; Olufikayo Bamidele (PLoS ONE)
Introduction Haematological malignancies are a heterogenous group of blood and lymphatic cancers. Survivorship care is a similarly diverse term concerning patients' health and wellbeing from diagnosis to end of life. Survivorship care for patients with haematological malignancies has traditionally been consultant-led and secondary care-based, although shifts away from this model have been occurring, largely via nurse-led clinics and interventions with some remote monitoring. However, there remains a lack of evidence regarding which model is most appropriate. Although previous reviews exist, patient populations, methodologies, and conclusions are varied, and further high-quality research and evaluation has been recommended. Aims The aim of the scoping review this protocol describes is to summarise current evidence on the provision and delivery of survivorship care for adult patients diagnosed with a haematological malignancy, and to identify existing gaps to inform future research. Methodology A scoping review will be carried out utilising Arksey and O'Malley's guidelines as its methodological framework. Studies published in the English language from December 2007 to the present will be searched on bibliographic databases, including Medline, CINAHL, PsycInfo, Web of Science, and Scopus. Papers' titles, abstracts, and full text will predominantly be screened by one reviewer with a second reviewer blind screening a proportion. Data will be extracted using a customised table developed in collaboration with the review team, and presented in tabular and narrative format, arranged thematically. Studies included will contain data regarding adult (25+) patients diagnosed with any haematological malignancy in combination with aspects related to survivorship care. The survivorship care elements could be delivered by any provider within any setting, but should be delivered pre- or post-treatment, or to patients on a watchful waiting pathway. Registration The scoping review protocol has been registered on the Open Science Framework (OSF) repository Registries (https://osf.io/rtfvq; DOI: 10.17605/OSF.IO/RTFVQ).